CORRECTIVE MAINTENANCE POMPA SENTRIFUGAL P-14 AVAK - Hoten, Hendri Van; Putra, Andrio Rama; Nurbaiti, Nurbaiti (UNIB Press, 2021)
PT. XYZ is one of UVW’s 6 Refinery Units that the main business is process crude oil and intermediate product (Alkylfeed, HSDC, slop oil, LOMC, Long residue, Raw PP) become finish product. One of the important equipments is pump that the example type is AVAK P-14 Centrifugal pump which is located in the Oil Pump House section. The problem is that there is a bend in the shaft due to lack lubrication on the bearing. Because of that, the pump is difficult to rotate by the motor that it occur stuck. The method solve the problem by using visual inspection and measuring dimension. The result is that pump has a bend in the shaft due to lack of lubrication in the bearing so heat due to friction between the shaft and the bearing which continue to rotate at high speed. In overcoming this problem, re-measurement dimension of pump and carried out suitable handling of the damaged pump components.